What are pollution, smoke, smog, and more... - Sharma, Richa (New Delhi The Energy Resources Institute, 2013)
Cars and factories keep spewing fumes into the air.Pollutants are destroying the ozone layer that protects us from the sun?s harmful ultraviolet rays. And greenhouse gases are causing the earth?s temperature to rise. Get to know more about air pollution so that you can protect the planet now.
Keywords: Air Pollution